2018
DOI: 10.3390/cryst8120463
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Nanoscale Abrasive Wear of Polycrystalline Silicon

Abstract: In this work, molecular dynamics simulations of the nanoscratching of polycrystalline and singlecrystalline silicon substrates using a single-crystal diamond tool are conducted to investigate the grain size effect on the nanoscale wear process of polycrystalline silicon. We find that for a constant indentation depth, both the average normal force and friction force are much larger for single-crystalline silicon compared to polycrystalline silicon. It is also found that, for the polycrystalline substrates, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Fluctuations in the friction force and sliding speed similar to that observed here have also been reported in studies of dry friction. ,, The same studies also show similar trends and magnitudes in friction values. Previous studies , of dry contacts also identified surface deformation caused by carbon-based nanoparticles confined between sliding surfaces.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Fluctuations in the friction force and sliding speed similar to that observed here have also been reported in studies of dry friction. ,, The same studies also show similar trends and magnitudes in friction values. Previous studies , of dry contacts also identified surface deformation caused by carbon-based nanoparticles confined between sliding surfaces.…”
Section: Resultssupporting
confidence: 87%
“…Although there are many MD simulations in the literature that have reported on the impacts of nanoparticles on surface friction, ,, the majority of them consider dry sliding conditions while ignoring the potential influence of electrostatics of nanoparticles near the sliding surfaces. References and , for example, reported MD simulations of dry friction levels for ND tips sliding on iron-, , silicon-, and carbon-based , surfaces. References and explored dry friction of carbon-based nanoparticles confined in sliders.…”
Section: Introductionmentioning
confidence: 99%
“…For nanoscratching on an atomistic flat surface, worn atoms can be evaluated as the atoms located above the original substrate surface [ 37 ]. Herein, we adopted a threshold height [ 38 ] to determine the worn atoms.…”
Section: Methodology and Model Descriptionmentioning
confidence: 99%
“…Single-crystal silicon is the key essential material of semiconductors with outstanding electrical properties and photovoltaic characteristics and has been widely used in the fields of optoelectronics and microelectronic devices [1]. However, it is difficult to fabricate highprecision microstructures of silicon wafer due to its high degree of hardness (12)(13)(14) and low level of fracture toughness (~1 MPa•m (1/2) ), which leads to significant restriction in the applications of conventional mechanical machining technologies like turning, milling, or grinding [2]. Ehmann et al [3] proposed a novel type of underwater micromachining process, laser-induced plasma micromachining (LIPMM), to fabricate microchannels on the silicon surface through high-temperature spot plasma in the liquid.…”
Section: Introductionmentioning
confidence: 99%